(untitled) (Journal of human and social sciences, 2016)
The thinker Malek Bennabi (1905–1973) presents a set of issues and ideas that he sees as organically linked to our cultural and civilizational life. In this regard, he observes that the process of change must necessarily affect the world of ideas, the world of people, and the world of things, if it is to succeed, for these are what can lead us to a stage of takeoff and civilizational revival. The social reconstruction of the Arab Muslim individual is, in his view, the first step toward renewing the network of social relations among Arab and Islamic peoples, so that confidence in our past and in the effectiveness of our Islamic values may be restored. Within this framework, we seek to shed light on one of the issues that preoccupied Malek Bennabi as he searched for the best ways to develop Islamic society.